The Evolution of Behavioral Accounting Research: A 25-Year Bibliometric Analysis - Pondrinal, Muhammad; Wahyudi, Rahmat; Luthan, Elvira (Economics, Business, Accounting & Society Review, 2025)
The development of accounting science increasingly highlights the strong interconnection between technical aspects and human behavior in decision-making, giving rise to the field of Behavioral Accounting. This study aims to analyze research trends in Behavioral Accounting using a bibliometric approach. The method employed is bibliometric analysis based on publication data from the Dimensions database for the period 2000–2024, with scientific mapping visualized using VOSviewer software. The analysis covers 6,109 peer-reviewed journal articles selected through relevant keywords, including bibliographic coupling by country, institution, journal, publication, and keyword co-occurrence. The results reveal that the United States is the dominant contributor in terms of publication volume and collaborative strength, followed by the United Kingdom, Australia, and Canada. Harvard University and the University of California, Los Angeles are identified as the most productive institutions, while Behavioral Research in Accounting emerges as the leading journal in this field. The publication by Libby (2002) holds a central position, serving as a key theoretical reference and bridging various generations of literature. These findings underscore that the academic landscape of Behavioral Accounting remains largely dominated by developed countries and prominent institutions, while developing countries such as Indonesia need to improve publication quality and enhance international collaboration. The implication of this study is the provision of a comprehensive knowledge map that can serve as a foundation for future research direction and foster broader engagement from the global academic community in the advancement of Behavioral Accounting.